As relações entre a maturidade da governança e a efetividade na gestão pública: estudo em uma rede de saúde municipal - Oliveira, Fernando Antônio Costa de (2024)
In public management, one of the challenges is the consolidation of the governance process, particularly regarding its relationship with the effectiveness of services provided, including in the field of health. In this context, the objective of this research is to investigate the relationships between the maturity of governance, in the dimensions of leadership, strategy and control, and the effectiveness of the municipal public health service. This is an exploratory-descriptive research, of a quantitative nature, carried out at the Municipal Health Department of Fortaleza/Ce. Primary data were collected through a questionnaire, with the results submitted to Spearman correlation analysis, involving the governance constructs adopted in the research (leadership, strategy and control) and the effectiveness construct. Secondary data were collected from public documents, with emphasis on laws, decrees, manuals and reports from the Court of Auditors of the State of Ceará. The organizational maturity reference adopted is the Governance and Management Index (iGG), from the Federal Court of Auditors. The effectiveness benchmark is the Municipal Management Effectiveness Index – IEGM, adopted by the Court of Auditors of the State of Ceará. Regarding the results obtained in the leadership/effectiveness analysis, it was found that 95.42% of the correlations reject the null hypothesis, 41.78% of the correlations are positive and 57.53% are negative correlations. Regarding strategy/effectiveness correlations, it appears that 85.43% of correlations reject the null hypothesis, 28.85% of correlations are positive and 53.78% are negative correlations. Regarding control/effectiveness correlations, it is observed that 89.07% of the correlations reject the null hypothesis, 37.73% of the correlations are positive and 62.26% are negative correlations. From the quantitative analysis carried out, it is concluded that despite having lower percentages, the positive correlations are considerable, and the operationalization of the governance dimensions used by the TCU contributes to the performance of the public health service analyzed, although it was not the focus of this research to infer about the cause and effect relationship of constructs.